2012
DOI: 10.1007/bf03392280
|View full text |Cite
|
Sign up to set email alerts
|

Operant variability: A conceptual analysis

Abstract: Some researchers claim that variability is an operant dimension of behavior. The present paper reviews the concept of operant behavior and emphasizes that differentiation is the behavioral process that demonstrates an operant relation. Differentiation is conceived as change in the overlap between two probability distributions: the distribution of reinforcement probability as a function of some response property (S distribution) and the probability distribution of the response property itself (R distribution). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
(27 reference statements)
0
14
0
6
Order By: Relevance
“…Barba (2012) pointed out that the calculation of U-values based on the complete set of possible response options or categories might not be appropriate when only some of the options are used. The second analysis confirmed his concern.…”
Section: Discussionmentioning
confidence: 99%
“…Barba (2012) pointed out that the calculation of U-values based on the complete set of possible response options or categories might not be appropriate when only some of the options are used. The second analysis confirmed his concern.…”
Section: Discussionmentioning
confidence: 99%
“…Although Machado observes variability that he cannot account for, he writes that "we cannot rule out the hypothesis that [schedule-behavior dynamics] underlay the differences in the degree of sequence variability across the three experiments" (p. 22). Barba (2012) is even more forceful in claiming that behavioral variability must be explainable: "Even if a contingency increases levels of behavioral variability but in fact differentially reinforces some sequences on the basis of properties other than their variability, the increase in variability levels, whatever it is, does not allow one to measure a differentiation process. In this case, the increase in variability represents a secondary effect of differential reinforcement" (p. 222, italics mine).…”
Section: Residuals: the Undiscovered Countrymentioning
confidence: 99%
“…demonstrated that behavioral variability can be selected by its consequences and suggested that variability is an operant dimension of behavior. Despite some alternative analyses of this issue (Barba, 2012a(Barba, , 2012b(Barba, , 2014Machado, 1989Machado, , 1992Machado, , 1993Machado, , 1997Machado & Tonneau, 2012), the operant variability interpretation has been largely supported across the years (for a review, see Neuringer & Jensen, 2012). Most studies have investigated the selection of variable behavior patterns by positive reinforcement contingencies (Neuringer & Jensen, 2012).…”
mentioning
confidence: 99%